2015
DOI: 10.1016/j.pneurobio.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic clustering within dendrites: An emerging theory of memory formation

Abstract: It is generally accepted that complex memories are stored in distributed representations throughout the brain, however the mechanisms underlying these representations are not understood. Here, we review recent findings regarding the subcellular mechanisms implicated in memory formation, which provide evidence for a dendrite-centered theory of memory. Plasticity-related phenomena which affect synaptic properties, such as synaptic tagging and capture, synaptic clustering, branch strength potentiation and spinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
144
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(155 citation statements)
references
References 161 publications
(302 reference statements)
9
144
2
Order By: Relevance
“…The notion that dendrites may act as semi-independent computational and storage units (Mel, 1992, Poirazi and Mel, 2001), together with evidence for dendritically localized synaptic plasticity (Govindarajan et al., 2011, Hardie and Spruston, 2009, Kang and Schuman, 1996), has led to multiple hypotheses regarding the role of dendritic plasticity in the formation of memory engrams (Branco and Häusser, 2010, Govindarajan et al., 2006, Kastellakis et al., 2015, Rogerson et al., 2014, Zhou et al., 2009). Modeling studies have only recently begun to investigate this issue, albeit using simplified models and/or focusing on single plasticity rules (Legenstein and Maass, 2011, O’Donnell and Sejnowski, 2014, Wu and Mel, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that dendrites may act as semi-independent computational and storage units (Mel, 1992, Poirazi and Mel, 2001), together with evidence for dendritically localized synaptic plasticity (Govindarajan et al., 2011, Hardie and Spruston, 2009, Kang and Schuman, 1996), has led to multiple hypotheses regarding the role of dendritic plasticity in the formation of memory engrams (Branco and Häusser, 2010, Govindarajan et al., 2006, Kastellakis et al., 2015, Rogerson et al., 2014, Zhou et al., 2009). Modeling studies have only recently begun to investigate this issue, albeit using simplified models and/or focusing on single plasticity rules (Legenstein and Maass, 2011, O’Donnell and Sejnowski, 2014, Wu and Mel, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions of the processes that link and organize memories are likely to affect cognitive function and result in psychopathology. For example, it has been proposed that molecular and cellular disruptions leading to over- or under-clustering may be related to the cognitive symptoms with a number of psychiatric problems, such as schizophrenia (memory interference caused by over-clustering) or autism (difficulty in contextual processing caused by under-clustering) (Kastellakis et al., 2015). Future experiments that test predictions proposed here will address the mechanisms underlying these pathologies in animal models, and therefore open new avenues for the understanding and treatment of memory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Our new 3D scanning methods, with preserved high spatial and temporal resolution, provide the missing tool for these activity measurements. Among other advantages, it will be possible to use these methods to investigate the origin of dendritic regenerative activities (Schiller et al., 2000, Larkum et al., 2009); the propagation of dendritic spikes (Katona et al., 2011, Chiovini et al., 2014, Fernández-Alfonso et al., 2014); spatiotemporal clustering of different input assemblies (Larkum and Nevian, 2008, Katona et al., 2011); associative learning (Kastellakis et al., 2015); the spatial and temporal structure of the activity of spine, dendritic, and somatic assemblies (Ikegaya et al., 2004, Takahashi et al., 2012, Villette et al., 2015); receptive field structures (Ohki et al., 2005); and function and interaction of sparsely distributed neuronal populations, such as parvalbumin-, somatostatin-, and VIP-expressing neurons (Klausberger and Somogyi, 2008, Kepecs and Fishell, 2014). Importantly, these complex functional questions can be addressed using our methods at the cellular and subcellular level, and simultaneously at multiple spiny (or aspiny) dendritic segments and at the neuronal network level in behaving animals.…”
Section: Discussionmentioning
confidence: 99%
“…In general, branch-specific plasticity can increase considerably the amount of information storage represented by single neurons and ultimately by the network (Poirazi et al, 2003a(Poirazi et al, , 2003bKastellakis et al, 2015). A leading theory is that the anatomical dendritic structure combined with the nonlinear properties of thin dendrites and especially the ability to generate local NMDA spikes enables pyramidal neurons to perform local computations and storage of information in small dendritic sub-compartments (Mel, 1992;Polsky et al, 2004;Major et al, 2013).…”
Section: Compartmentalized Plasticity Mechanismsmentioning
confidence: 99%
“…For example, whereas synapses innervating proximal basal dendrite undergo spike-timingdependent plasticity (STDP) when paired with BAPs, synapses innervating distal basal dendrites undergo plasticity when paired with local NMDA spikes and in the presence of brain-derived neurotrophic factor (BDNF) (Gordon et al, 2006). In addition to long-term changes in synaptic strength, recent studies indicated that intrinsic dendritic excitability may also undergo plasticity changes that can serve as a powerful mechanism for modulating integration of synaptic inputs and ultimately dynamically change the neuronal output (Frick et al, 2004;Remy et al, 2010;Kastellakis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%